1997 Proceedings 47th Electronic Components and Technology Conference
DOI: 10.1109/ectc.1997.606188
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic solder flip chip technology-bumping and assembly process development for CSP/BGA

Abstract: Eutectic solder flip chip fabrication technology, through bumping to assembly process, has been developed. In bumping process, electroplating method and thick photo resist process could form eutectic solder bumps whose uniformity of height are less than 10 % within wafer. Eutectic solder flip chip assembly process, which includes bonding, cleaning and underfilling, has been also developed. Bonding process of eutectic solder indicates good self-alignment. The excellent rosin cleaning was achieved by the ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The resulting completed flip chip assembly is much smaller than a traditional carrier-based system; the chip sits directly on the circuit board, and is much smaller than the carrier both in area and height. The short wires greatly reduce inductance, allowing higher-speed signals, and also conduct heat better [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting completed flip chip assembly is much smaller than a traditional carrier-based system; the chip sits directly on the circuit board, and is much smaller than the carrier both in area and height. The short wires greatly reduce inductance, allowing higher-speed signals, and also conduct heat better [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Sn-Ag solder bump heights were measured by a focus point detection method. For higher reliable CSP packages, bump heights of more than 70 pm as reflowed are necessary [3,4]. The present bump process can easily provide the required bump heights.…”
Section: Figure 2 Cross-sectional Sem View Of the Plating Maskmentioning
confidence: 97%
“…We previously reported that the novel eutectic Sn-Pb alloy electroplated bump process is well qualified to have high reliable flip chip interconnection for CSPs and BGAs [4,5,6]. The current environmentally conscious manufacturing moves towards Pb-free schemes for electronic devices and components.…”
Section: Introductionmentioning
confidence: 99%